1
$\begingroup$

I want to write as a sigle summation of \begin{align*} \sum_{k=0}^{n}\binom{n}{k} \pi^{n-k}(\cot\alpha)^{k}-\sum_{k=0}^{n+1}\binom{n+1}{k} \pi^{n+1-k}(\cot\alpha)^{k}. \end{align*} How to change upper limit of any one of the summations?

$\endgroup$
5
$\begingroup$

You can use Binomial theorem, then given expression will be:

$$(\pi+\cot \alpha)^n-(\pi+\cot \alpha)^{n+1}=(1-\pi-\cot \alpha)(\pi+\cot \alpha)^n$$

Now, use the Binomial theorem to get a single summation.

$\endgroup$
  • 1
    $\begingroup$ +1 I totally didn't recognize the binomial theorem for some reason. $\endgroup$ – orlp Oct 9 '17 at 15:00
5
$\begingroup$

$$\sum_{k=0}^{n}\binom{n}{k} \pi^{n-k}(\cot\alpha)^{k}-\sum_{k=0}^{n+1}\binom{n+1}{k} \pi^{n+1-k}(\cot\alpha)^{k} = $$

$$\sum_{k=0}^{n}\binom{n}{k} \pi^{n-k}(\cot\alpha)^{k}-\sum_{k=0}^{n}\binom{n+1}{k} \pi^{n+1-k}(\cot\alpha)^{k} - \binom{n+1}{n+1}\pi^0(\cot \alpha)^{n+1} = $$

$$\sum_{k=0}^{n} \left[\binom{n}{k} \pi^{n-k} - \binom{n+1}{k} \pi^{n+1-k}\right ](\cot\alpha)^{k} - (\cot \alpha)^{n+1} = $$

$$ - (\cot \alpha)^{n+1} + \sum_{k=0}^{n} \left[\binom{n}{k} - \pi\binom{n+1}{k}\right ]\pi^{n-k}(\cot\alpha)^{k}$$

Or, arguably better as Arun Badajena notices:

$$\sum_{k=0}^{n}\binom{n}{k} \pi^{n-k}(\cot\alpha)^{k}-\sum_{k=0}^{n+1}\binom{n+1}{k} \pi^{n+1-k}(\cot\alpha)^{k} = $$

$$(\pi + \cot\alpha)^n - (\pi + \cot\alpha)^{n+1} =$$ $$(1 - \pi - \cot\alpha)(\pi + \cot\alpha)^n = $$ $$(1 - \pi - \cot\alpha)\sum_{k=0}^{n}\binom{n}{k} \pi^{n-k}(\cot\alpha)^{k} $$

$\endgroup$
1
$\begingroup$

Second term, evaluated up to $n$ in the sum and then placing out the $k=n+1$ term.

\begin{align*} \sum_{k=0}^{n+1}\binom{n+1}{k} \pi^{n+1-k}(\cot\alpha)^{k} &= \sum_{k=0}^{n}\binom{n+1}{k} \pi^{n+1-k}(\cot\alpha)^{k} +\cot^{n+1} \alpha \end{align*}

$\endgroup$
1
$\begingroup$

You can just split off the last term of the second sum $$\begin{align*} \sum_{k=0}^{n}\binom{n}{k} \pi^{n-k}(\cot\alpha)^{k}-\sum_{k=0}^{n+1}\binom{n+1}{k} \pi^{n+1-k}(\cot\alpha)^{k} \\ = \sum_{k=0}^{n}\binom{n}{k} \pi^{n-k}(\cot\alpha)^{k}-\sum_{k=0}^{n}\binom{n+1}{k} \pi^{n+1-k}(\cot\alpha)^{k}-(\cot \alpha)^{n+1}\\ =\sum_{k=0}^{n}\left[\binom{n}{k}+\pi\binom{n+1}k\right] \pi^{n-k}(\cot\alpha)^{k}-(\cot \alpha)^{n+1} \end{align*}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.